Upaya meningkatkan kompetensi guru dalam menyusun rencana program pembelajaran harian melalui bimbingan berkelanjutan di TK negeri pembina Gubug - Fransisca Lilis Sutarsi (Universitas Sebelas Maret, 2023)
This school action research aims to increase teacher competency in preparing Daily Learning Implementation Plans through ongoing guidance at Pembina Gubug State Kindergarten, Grobogan District where the researcher works. This research was conducted at Pembina Gubug State Kindergarten, Gubug District, Grobogan District, for 3 (three) years the exact month from March to May 2023. The subjects of this study were all teachers at the Gubug Pembina State Kindergarten, Gubug sub-district, Grobogan Regency, totaling 5 (five) people. Data collection techniques using interviews, observation, and discussion. The research procedure is a series of research stages from start to finish. This research is a cyclical system review process as the framework developed by Suharsimi Arikuntodkk. This procedure includes the following stages: (1) planning, (2) implementing, (3) observing, (4) reflecting. Research is considered successful if the teacher's ability to prepare lesson plans can increase. It is shown by the existence of an average score, which at the beginning of the study resulted in at least 75% achievement in the Basic Competency Component, then in the second cycle if it was presented 100%, there was an increase of 25% from cycle 1. In the learning objectives component if it was presented 75%, then in the second cycle if it is presented 100%, there is an increase of 25% from cycle 1. The results of the study prove that continuous guidance can increase teacher competence in preparing Daily Learning Implementation Plans (RPPH) in the Gubug Pembina State Kindergarten, Gubug sub-district, Grobogan Regency. as evidenced by the results of the research before the action was carried out there were 2 (two) teachers who did not understand how to prepare an RPPH by going through various stages. After the ongoing guidance action was carried out, it increased so that from 5 teachers all understood how to prepare RPPH according to the correct stages.